Vertical distribution by demographic groups of ghost crab Ocypode quadrata (Crustacea: Brachyura) - Correa, Michele O. D. A. [UNESP]; Andrade, Luciana S. [UNESP]; Costa, Rogerio C. [UNESP]; Castilho, Antonio L. [UNESP]; Bertini, Giovana [UNESP]; Fransozo, Adilson [UNESP] (De Gruyter Open Ltd, 2014)
The ghost crab Ocypode quadrata plays an important role in energy transfer between trophic levels, and has been widely used in evaluations of impacted environments. In order to provide data on the biology of this potential bioindicator species, the population structure and vertical distribution of individuals were studied on two beaches in southeastern Brazil. Each beach was divided into quadrants of 1000 m(2) with boundaries of upper, middle and lower levels in relation to the waterline. Collected monthly by active searching through one year, the specimens of O. quadrata were sexed, measured for carapace width, and returned to the beach. Of the total of 1904 specimens collected, the largest proportion (46.2%) were males, followed by 31.4% juveniles. The vertical distribution of the ghost crabs differed among age groups: males mostly occupied the middle and upper levels; adult females, ovigerous or not, were more abundant in the lower level; and juveniles were evenly distributed in all levels, with a slight tendency toward the middle. The sex ratio favored males in a few months of the year and in the larger size classes. The abundance of O. quadrata is limited by low temperatures, and its spatial and temporal distribution is controlled by food availability and ease of reproduction. Knowledge of the biology of these crabs is essential in order to use them as a bioindicator species; the vertical distribution patterns may reflect changes in the beach hydrodynamics or other environmental factors.
Keywords: intertidal zone; Ocypode quadrata; Ocypodidae; population pattern; vertical migration